CCT3-LINC00326 axis regulates hepatocarcinogenic lipid metabolism. Issue 10 (12th January 2022) - Søndergaard, Jonas Nørskov; Sommerauer, Christian; Atanasoai, Ionut; Hinte, Laura C; Geng, Keyi; Guiducci, Giulia; Bräutigam, Lars; Aouadi, Myriam; Stojic, Lovorka; Barragan, Isabel; Kutter, Claudia
Abstract : Objective: To better comprehend transcriptional phenotypes of cancer cells, we globally characterised RNA-binding proteins (RBPs) to identify altered RNAs, including long non-coding RNAs (lncRNAs). Design: To unravel RBP-lncRNA interactions in cancer, we curated a list of ~2300 highly expressed RBPs in human cells, tested effects of RBPs and lncRNAs on patient survival in multiple cohorts, altered expression levels, integrated various sequencing, molecular and cell-based data. Results: High expression of RBPs negatively affected patient survival in 21 cancer types, especially hepatocellular carcinoma (HCC). After knockdown of the top 10 upregulated RBPs and subsequent transcriptome analysis, we identified 88 differentially expressed lncRNAs, including 34 novel transcripts. CRISPRa-mediated overexpression of four lncRNAs had major effects on the HCC cell phenotype and transcriptome. Further investigation of four RBP-lncRNA pairs revealed involvement in distinct regulatory processes. The most noticeable RBP-lncRNA connection affected lipid metabolism, whereby the non-canonical RBP CCT3 regulated LINC00326 in a chaperonin-independent manner. Perturbation of the CCT3- LINC00326 regulatory network led to decreased lipid accumulation and increased lipid degradation in cellulo as well as diminished tumour growth in vivo . Conclusions: We revealed that RBP gene expression is perturbed in HCC and identified that RBPs exerted additional functions beyond their tasks under normal physiological conditions, which can be stimulated or intensified via lncRNAs and affected tumour growth.